Using deception to establish a reproducible improvement in 4-km cycling time trial performance - Shei, R.-J.; Thompson, K.; Chapman, R.; Raglin, J.; Mickleborough, T. (International Journal of Sports Medicine, 2016)
We investigated whether performance gains achieved with deception persisted after the deception was revealed, and whether pacing strategy changed. 14 trained cyclists completed 4 simulated 4-km time trials (TT) on a cycle ergometer comprising familiarization and baseline trials (BAS), followed by "unaware" (of deception, UAW) and "aware" (of deception, AW) trials on separate days. In the UAW trial, participants competed against an on-screen avatar set at 102% of their baseline trial mean power output (Pmean) believing it was set at 100% of BAS Pmean. 24 h prior to the AW trial, participants were informed of the deception in the UAW trial. 4 participants did not improve in the UAW trial compared to BAS. 10 participants improved time to completion (TTC) and Pmean in the UAW and AW trials compared to BAS (p<0.03) with no significant differences between UAW and AW (p=1.0). Pacing strategy (at 0.5-km intervals) and RPE responses were unchanged (p>0.05) for these participants. In summary, deception did not improve performance in all participants. However, participants whose time trial performance improved following deception could retain their performance gains once the deception was revealed, demonstrating a similar pacing strategy and RPE response.